Patients’ Profile of Cleft Lip and Palate : 3 Years Evaluation at Surabaya CLP Center Foundation - Widjaja, Febe Alodia; Saputro, Iswinarno Doso (Jurnal Plastik Rekonstruksi, 2024)
Introduction: Cleft lip and cleft palate are the most common birth defects affecting newborns, yet their variability across each geographic origin is not clearly understood. This study aims to investigate the CL/P prevalence, profile, and corrective surgery timing in Surabaya, Indonesia.Method: This retrospective research used a descriptive method by collecting medical data records from the Surabaya CLP Center Foundation from January 2021 to December 2023, which related to sociodemographic problems, clinical features, and management timing were then statistically analyzed.Results: A total of 495 patients underwent cleft surgery, of which 59.4% were male and 40.6% were female. The most common type of Craniofacial Cleft observed is Combination Cleft Lip and Palate “CLP” (71.1%). CLP is more common in male patients than in female patients (43.4% vs. 27.7%); while CL is more common among males (14.1% vs. 9.7%) and CP is more common in females (3.2% vs. 1.8%). Significantly, complete clefts (72.9%) were more common than the incomplete clefts (27.1%). Unilateral clefts were more common than bilateral clefts (76.2% vs 18.8%). It was observed that only 22% of patients had a family history of CL/P. Overall, 74,9% of patients underwent corrective surgery within the right period.Conclusions: The data shows that most patients tended to seek medical advice and treatment at appropriate times, suggesting a high awareness of CLP as the result of proactive education and social outreach by the charity institution. Further investigations using data from other institutions are suggested to conclude the CLP management in Surabaya entirely.